Α-blockers and antibiotics, alone or in combination, improve symptoms in men with chronic prostatitis/chronic pelvic pain syndrome. Issue 5 (25th April 2011) - Perletti, Gianpaolo; Magri, Vittorio
Abstract : Commentary on: Anothaisintawee T Attia J Nickel JC . Management of chronic prostatitis/chronic pelvic pain syndrome: a systematic review and network meta-analysis. JAMA 2011 ;305 :78 –86 .